Ontogeneticl features of the secretory apparatus of rat atrial myocardium. - Shevchenko, K. M.; Tverdokhleb, I. V. (Морфологія / Morphologia / Morfologìâ, 2012)
The purpose of the research – ultrastructural and histochemical analysis of the secretory apparatus development of rat atrial myocardium. The highest secretory activity of the mature myocardium appears at the right ear of the heart due to the predominance of highly specialized secretory myocytes (over 75% of the myocyting population). Secretory activity of the mature areas of the myocardium decreases in the sequence: the left auricle - right atrium - the left atrium - interatrial septum - interventricular septum - right ventricle - the left ventricle. The development of the secretory apparatus on the stages of histogenesis of the myocardium based on the conversion of the quantitative relation between high and low specialized secretory cardiomyocytes. The highest rates of formation of heterogeneity secretory apparatus characteristic for myocardium of the right auricle of the heart while the lowest – for interatrial septum of the myocardium. Ventricular myocardium has a moderate secretory activity on the early postembryonic development of a rat; mature ventricular cardiomyocytes lose their secretory activity. Definitive level of heterogeneity of the secretory apparatus of the myocardium achieved by the end of the 1st month of postnatal ontogenesis of rats.